Resting hearing thresholds in children aged 7-10 years - Jaroszewski, A.; Rogowski, P.; Rakowski, A. (Archives of Acoustics, 2001)
Resting hearing thresholds were measured in 107 children in 7-10 years of age category, from primary schools in Warsaw. The children were recruited regardless of the priority of these in which problems with hearing acuity were observed or these in which such problems might have been expected on the grounds of their children-illness history. The measurements were performed with the use of tonal audiometry with intermittent 250/250ms signal, in the range of frequencies from 100Hz to 16kHz. In the children with deeper hearing loss, both air and bone conduction procedures were used. In the tested group normal hearing within [ampersand]plusmn;10dB was found in only 13% of the children. In the rest of the group hearing loss of various nature was found, i.e.: wideband hearing loss (8%), high frequency (24%), selective V-dip type (36%), low frequency (54%) and deep hearing loss of various configurations (16%). In the fraction with low frequency hearing loss often conductive hearing loss was found, whilst in the case of high frequency hearing loss, bone conduction audiometry indicated sensorineural type of hearing loss. High frequency hearing loss, selective and low frequency hearing loss in excess of 20dB was found in 25% of the children tested. In the fraction with deep hearing loss in 25% of the children tested, hearing loss of approximately 40dB was found.